2014
DOI: 10.1016/j.fluid.2013.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior and mesoscale solubilization in aqueous solutions of hydrotropes

Abstract: Hydrotropes are amphiphilic molecules that are too small to spontaneously form equilibrium structures in aqueous solutions, but form dynamic, non-covalent assemblies, referred to as clusters. In the presence of a hydrophobic compound, these clusters seem to get stabilized leading to the formation of long-lived, highly stable mesoscopic droplets, a phenomenon that we call "mesoscale solubilization". In this work, we focus on the unusual mesoscopic properties of aqueous solutions of a nonionic hydrotrope, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 54 publications
2
67
1
1
Order By: Relevance
“…[28,29,31,32]. In Moscow, the measurements were performed at the scattering angles of 20, 30 and 90 .…”
Section: Light Scatteringmentioning
confidence: 99%
See 3 more Smart Citations
“…[28,29,31,32]. In Moscow, the measurements were performed at the scattering angles of 20, 30 and 90 .…”
Section: Light Scatteringmentioning
confidence: 99%
“…It has been shown that such inhomogeneities occur in aqueous solutions of nonionic hydrotropes when the solution contains a third, more hydrophobic, component [12,13,[28][29][30][31][32]. Remarkably, these inhomogeneities (emerging in water-rich ternary systems) are only pronounced in the hydrotrope concentration range where molecular clustering and thermodynamic anomalies are observed in the original binary hydrotrope-water solutions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Положение указанной границы качественно совпало с ранее опубликованными данными [10]. Однако проведенное нами определение составов фаз расслоенной системы позволило установить, что положение критической точки расслоения существенно отли-чается от ранее опубликованного: на треугольной фазовой диаграмме системы критиче-ская точка смещена к вершине воды (см.…”
Section: результаты экспериментальных исследованийunclassified